Researching of Image Compression Based on Quantum BP Network - Yang Ran; Zuo Yanjun; Lei Wanjun (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The encoding time of traditional fractal image coding method is too long.Aiming at this problem, a quantum BP network algorithm is proposed in the paper. By using a neuronal model with quantum input and output, combined with the theory of BP in image compression and the complex BP algorithm, a model for image impression with 3-layer quantum BP is built, which implements image compression and image reconstruction. The simulation results show that QBP can obtain the reconstructed images with better quantity compared with BP in spite of the less learning iterations. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3550